Chronic intestinal immune activation reveals separable impacts of inflammation and barrier loss on hallmarks of ageing - Jeanette Alcaraz; Charlotte Keyse; Charles Hall; David W. Walker; David P. Doupé; Rebecca I. Clark (PLoS ONE, 2026)
Inflammaging is considered a driver of age-associated pathology across tissues. Similarly, intestinal permeability is a feature of ageing and underlies a range of inflammatory and age-related diseases. Increased intestinal permeability has been described as both a cause and a consequence of inflammation. Both intestinal permeability and inflammation are closely associated with microbial dysbiosis, epithelial dysplasia and mortality but dissecting the complex interplay between these phenotypes remains challenging. Here we genetically induce intestinal immune activation in Drosophila and stratify animals by their intestinal barrier status using the Smurf assay. We demonstrate that intestinal barrier failure has a distinct impact on the microbiota. Further, immune activation, both within the intestine and systemically, drives intestinal barrier failure and mortality even in the absence of the microbiota. Importantly, immune-induced intestinal barrier failure takes time to develop and is closely associated with the onset of mortality. Our work adds to building evidence that the impact of intestinal permeability on the microbiota and on animal health needs to be considered independently of its relationship with inflammation.